Analisis Model ROPE dalam Evaluasi Perencanaan City Branding “Lamongan Megilan” - Arlinda, Silvi; Harini, Setyasih; Pramudia, Christian Andhika (Jurnal Komunikasi Nusantara, 2025)
The application of city branding has become an essential strategy to strengthen regional competitiveness and identity, including Lamongan Regency with its slogan “Lamongan Megilan.” This study aims to evaluate the planning strategy of this city branding using the ROPE model (Research, Objectives, Programming, Evaluation), which provides a systematic framework for assessing each stage of planning. This qualitative research employs a constructivist paradigm, with data collected through in-depth interviews and documentation analyzed using interactive techniques. The study identifies strategic planning steps, evaluates the role of the Lamongan Regency Public Relations Department, and explores community involvement in implementing the program. The findings reveal proactive public relations activities, such as online dissemination and stakeholder collaboration. However, challenges persist in the limited regulatory framework and the lack of comprehensive socialization of the “Megilan” slogan. Training for Public Relations personnel is needed to enhance communication management competencies. In conclusion, “Lamongan Megilan” has strong potential to enhance Lamongan’s image and appeal, but requires more integrated planning through regulatory support, capacity building, and creative communication strategies. The study recommends strengthening regional policies and communication efforts for sustainable city branding implementation. Abstrak Penerapan konsep city branding menjadi strategi penting dalam memperkuat daya saing dan identitas daerah, termasuk Kabupaten Lamongan dengan slogan “Lamongan Megilan.” Penelitian ini bertujuan untuk mengevaluasi strategi perencanaan city branding tersebut menggunakan model ROPE (Research, Objectives, Programming, Evaluation) yang menyediakan kerangka kerja sistematis untuk menilai setiap tahapan perencanaan. Penelitian ini menggunakan metode kualitatif dengan paradigma konstruktivis, di mana data dikumpulkan melalui wawancara mendalam dan dokumentasi, kemudian dianalisis dengan teknik analisis interaktif. Fokus penelitian mencakup identifikasi langkah strategis, evaluasi peran Humas Kabupaten Lamongan, serta keterlibatan masyarakat dalam pelaksanaan program. Hasil penelitian menunjukkan aktivitas Humas yang bersifat proaktif, seperti penyebarluasan informasi melalui media daring dan kolaborasi dengan berbagai pemangku kepentingan. Namun, tantangan masih ditemukan pada aspek regulasi yang belum optimal dan kurangnya sosialisasi mendalam mengenai makna slogan “Megilan.” Diperlukan pelatihan bagi personel Humas untuk meningkatkan kompetensi dalam manajemen komunikasi. Kesimpulannya, city branding “Lamongan Megilan” memiliki potensi besar untuk memperkuat citra dan daya tarik daerah, namun memerlukan perencanaan yang lebih terintegrasi melalui dukungan regulasi, peningkatan kapasitas, serta strategi komunikasi yang kreatif.